التباس مفهوم الشرعية الدوليّة في ظل النّظام الدولي الراهن - يورفلي, خضر; هرمز, نور الدين; قنوع, صقر (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يحاول هذا البحث مناقشة مسألة من أهمّ المسائل التي تنشغل بها المنتديات والمنابر الدولية على اختلاف مشاربها، تلك المتمثّلة بالتّعمية والالتباس الحاصل في مفهوم الشّرعيّة الدوليّة، واهتزاز مصداقيّة المنظّمة الدّوليّة التي تمثّل عصب النظام الدّولي الراهن، وعليه سنبحث هذا الموضوع من خلال ثلاثة محاور أساسيّة أوّلها: مسألة القطبيّة الدّوليّة أهي أحاديّة أم تعددية؟، والثاني مسألة الشرعيّة الدوليّة من زاوية قانونيّة وميثاقيّة، والمحور الثالث صور ومظاهر الانحراف الحاصلة بالشرعيّة الدوليّة والتي أدّت إلى زيادة بؤر التوتّر على المسرح الدّولي، وأظهرت عقم ومحدوديّة دور الأمم المتحدة في إيجاد الحلول لها.This research attempts to discuss the issue of the most important issues which concern to the international forums and platforms on their different backgrounds and those of Cryptography and confusion winning in the concept of international legitimacy and the credibility and the vibration of international organization that represents the backbone of the current international system. Therefore, we will explore this topic through three main axes: firstly the issue of International Polar Is it single or multi-party, and the second issue of the international legitimacy of the legal and chartered items angle, and Axis III: aspeds and manifestations of deviation winning in the international legitimacy and which led to the increase of hotspot of tension on the international stage and showed the futility and the limited role of the United Nations in finding solutions to them.